Assessment of the geolocation accuracy of YG-13A high-resolution SAR data. Issue 2 (1st February 2018) - Deng, Mingjun; Zhang, Guo; Zhao, Ruishan; Zhang, Qingjun; Li, Deren; Li, Jiansong
ABSTRACT: The YG-13A mission, launched in late 2015, is the first Chinese synthetic aperture radar (SAR) satellite to achieve sub-meter resolution. In this paper, we briefly introduce this milestone satellite and describe a method for improving YG-13A's absolute positioning accuracy. We evaluated the plane and three-dimensional absolute positioning accuracy over five test sites. The results indicate that high-accuracy absolute positioning can now be achieved with a horizontal accuracy of 3 m or better for strip-map data and 2 m or better for sliding spot data, without regard to the elevation error. In addition, the three-dimensional absolute positioning accuracy in plane and elevation is within 3 m and 2 m, respectively, which satisfies the requirements for high-precision three-dimensional control points.